2014
DOI: 10.1007/s00339-014-8721-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene glycol-assisted solvothermal fabrication of ZnWO4 nanostructures with tunable size, optical properties, and photocatalytic activities

Abstract: Large scale of uniform small ZnWO 4 nanocrystals and ZnWO 4 nanorods with tunable size have been fabricated in ethylene glycol (EG)-assisted solvothermal process, ZnWO 4 samples ranging in shape from tiny nanocrystals to nanorods were dependent on the volume ratio of EG and water (H 2 O). The optical properties of ZnWO 4 nanocrystals and nanorods were investigated by photoluminescence (PL) spectroscopy, showing longer ZnWO 4 nanorods own the increased PL intensity in comparison with that of shorter ones and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 41 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…For example, ZnWO4 nanoparticles and nanorods were successfully synthesized via kinetic and thermodynamic control processes by hydrothermal method, and it was demonstrated that the perfect crystallinity of ZnWO4 nanorods can enhance the photocatalytic activity [10]. ZnWO4 with cubic morphology [16], nanocrystals [21], yolk-shell microspheres [20], nanorods with different aspect ratio [22] were also synthesized for photocatalysis application in recent years. The effects of morphology on the photocatalytic activity of ZnWO4 are also discussed in several studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ZnWO4 nanoparticles and nanorods were successfully synthesized via kinetic and thermodynamic control processes by hydrothermal method, and it was demonstrated that the perfect crystallinity of ZnWO4 nanorods can enhance the photocatalytic activity [10]. ZnWO4 with cubic morphology [16], nanocrystals [21], yolk-shell microspheres [20], nanorods with different aspect ratio [22] were also synthesized for photocatalysis application in recent years. The effects of morphology on the photocatalytic activity of ZnWO4 are also discussed in several studies.…”
Section: Introductionmentioning
confidence: 99%